Atomic Force Microscopy and Infrared Nanospectroscopy of COVID-19 Spike Protein for the Quantification of Adhesion to Common Surfaces - O'Callahan, Brian (Langmuir : the ACS journal of surfaces and colloids, 2021)
The COVID-19 pandemic has claimed millions of lives worldwide, sickened many more, and has resulted in severe socioeconomic consequences. As society returns to normal, understanding the spread and persistence of SARS CoV-2 on commonplace surfaces can help to mitigate future outbreaks of coronaviruses and other pathogens. We hypothesize that such an understanding can be aided by studying the binding and interaction of viral proteins with nonbiological surfaces. Here, we propose a methodology for investigating the adhesion of the SARS CoV-2 spike glycoprotein on common inorganic surfaces such as aluminum, copper, iron, silica, and ceria oxides as well as metallic gold. Quantitative adhesion was obtained from the analysis of measured forces at the nanoscale using an atomic force microscope operated under ambient conditions. Without imposing further constraints on the measurement conditions, our preliminary findings suggest that spike glycoproteins interact with similar adhesion forces across the majority of the metal oxides tested with the exception to gold, for which attraction forces ∼10 times stronger than all other materials studied were observed. Ferritin, which was used as a reference protein, was found to exhibit similar adhesion forces as SARS CoV-2 spike protein. This study results show that glycoprotein adhesion forces for similar ambient humidity, tip shape, and contact surface are nonspecific to the properties of metal oxide surfaces, which are expected to be covered by a thin water film. The findings suggest that under ambient conditions, glycoprotein adhesion to metal oxides is primarily controlled by the water capillary forces, and they depend on the surface tension of the liquid water. We discuss further strategies warranted to decipher the intricate nanoscale forces for improved quantification of the adhesion